IMPLICATURE ANALYSIS OF ABDUR’S STAND UP COMEDY ON KOMPAS TV - Aulia Helena Putri Lesmana (ReALL - Research on Applied Linguistics and Literature, 2022)
This study tries to analyze the implicature in Abdur’s stand-up comedy on Kompas TV specifically to explore the types of implicature and the most dominant type of implicature used. A qualitative descriptive study with observation and note taking technique instrument were employed in this study. The result of the analysis showed that of the 11 data found, 4 data are conventional implicatures and 7 data are conversational implicatures. the number of occurrences of the most dominant type of implicature is conversational implicature (conventional implicature) with 7 data. This shows that the speech in Abdur's stand-up comedy contains many implications with the meaning of the word itself.